Peran Orang Tua dalam Meminimalisasi Kasus Perundungan Anak di Sekolah Dasar - Fauziyah, Syifa Hasna; Sutini, Ai (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
The rise of bullying cases is increasing and has become a pressing issue in today's society. The problem of bullying does not only occur among adolescents, but many occur in the elementary school environment. One of the preventions in minimizing cases of bullying in children is the very important role of parents. Parents play a big role in helping children to have good character and personality. This research aims to find out how the role of parents in minimizing cases of child bullying, especially in elementary schools. This research uses the literature study method by using data and information through several research sources. The results of this study show that the role of parents is very important because they are the first agent in shaping children's character, morality and skills. Therefore, parents must know their role as mentors, educators, and protectors, because it will have an impact on the welfare of children and help minimize the occurrence of bullying.